Plant species–area relationships are determined by evenness, cover and aggregation in drylands worldwide. Issue 3 (11th December 2018) - DeMalach, Niv; Saiz, Hugo; Zaady, Eli; Maestre, Fernando T.
Abstract: Aim: Species–area relationships (also known as "species–area curves" and "species accumulation curves") represent the relationship between species richness and the area sampled in a given community. These relationships can be used to describe diversity patterns while accounting for the well‐known scale‐dependence of species richness. Despite their value, their functional form and parameters, as well as their determinants, have barely been investigated in drylands. Location: 171 drylands from all continents except Antarctica. Time period: 2006–2013. Major taxa studied: Perennial plants. Methods: We characterized species–area relationships of plant communities by building accumulation curves describing the expected number of species as a function of the number of sampling units, and later compared the fit of three functions (power law, logarithmic and Michaelis–Menten). We tested the prediction that the effects of aridity, soil pH on the species–area relationship (SAR) are mediated by vegetation attributes such as evenness, cover and spatial aggregation. Results: We found that the logarithmic relationship was the most common functional form ( c . 50%), followed by Michaelis–Menten ( c . 33%) and power law ( c . 17%). Functional form was mainly determined by evenness. Power‐law relationships were found mostly under low evenness, logarithmic relationships peaked under intermediate evenness and the Michaelis–Menten function increased in frequency with increasing evenness. The SAR parameters approximated by the logarithmic model ["small‐scale richness" ( b 0 ) and "accumulation coefficient" ( b 1 )] were determined by vegetation attributes. Increasing spatial aggregation had a negative effect on the small‐scale richness and a positive effect on the accumulation coefficient, while evenness had an opposite effect. In addition, the accumulation coefficient was positively affected by cover. Interestingly, increasing aridity decreased small‐scale richness but did not affect the accumulation coefficient. Main conclusions: Our findings highlight the role of evenness, spatial aggregation and cover as the main drivers of SARs in drylands, the Earth's largest biome.